2014
DOI: 10.1186/1750-1172-9-49
|View full text |Cite
|
Sign up to set email alerts
|

X-exome sequencing in Finnish families with Intellectual Disability - four novel mutations and two novel syndromic phenotypes

Abstract: BackgroundX-linked intellectual disability (XLID) is a group of genetically heterogeneous disorders characterized by substantial impairment in cognitive abilities, social and behavioral adaptive skills. Next generation sequencing technologies have become a powerful approach for identifying molecular gene mutations relevant for diagnosis.Methods & objectivesEnrichment of X-chromosome specific exons and massively parallel sequencing was performed for identifying the causative mutations in 14 Finnish families, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 44 publications
8
69
0
6
Order By: Relevance
“…These findings are consistent with earlier electrophysiological studies showing that SAP102 regulates glutamate receptor trafficking during synaptogenesis (8). Interestingly, mutations in the human gene encoding SAP102 are associated with X-linked intellectual dis-ability, which is often associated with dendritic spine abnormalities (45)(46)(47). Protein products of all identified SAP102 mutant alleles lack the SH3 and GK domains, which could lead to mislocalization of the truncated SAP102 protein and disruption of the downstream signaling of NMDARs.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with earlier electrophysiological studies showing that SAP102 regulates glutamate receptor trafficking during synaptogenesis (8). Interestingly, mutations in the human gene encoding SAP102 are associated with X-linked intellectual dis-ability, which is often associated with dendritic spine abnormalities (45)(46)(47). Protein products of all identified SAP102 mutant alleles lack the SH3 and GK domains, which could lead to mislocalization of the truncated SAP102 protein and disruption of the downstream signaling of NMDARs.…”
Section: Discussionsupporting
confidence: 90%
“…For the GRIA gene family, there have been reports of a fusion transcript in GRIA2, a de novo interstitial deletion of chromosome 4q32 that contains the GRIA2 loci, missense mutations in the ligand binding and transmembrane domains of the GluA3 subunit (GRIA3), partial tandem duplication that reduced GRIA3 transcript levels, as well as frameshift in the GRIA3 gene ( Fig. 5; Supplemental Table S3) (Chiyonobu et al, 2007;Wu et al, 2007;Bonnet et al, 2009Bonnet et al, , 2012Poot et al, 2010;Tzschach et al, 2010;Hackmann et al, 2013;Philips et al, 2014). These data suggest that mutations within the GRIA gene family participate in a small subset of patients with intellectual disability; however, few cellular or mechanistic studies of these modifications have been reported.…”
Section: Ampa-selective Glutamate Receptorsmentioning
confidence: 99%
“…We have also compiled the rare non-synonymous variants identified in FMR1 during large-scale studies (large panel, X-exome or wholeexome sequencing) performed on ID patients by other teams: only missense variants but no truncating variants were identified in the 3180 individuals tested. [33][34][35][36][37][38][39][40][41][42] We reanalyzed all these variants in FMR1 in the light of new public sequencing data (Exome Variant Server and the ExAC project, supposed to be free or at least not enriched in severe developmental disorders), prediction tools and functional evidence. Altogether, six previously reported variants could also be reclassified as disease-causing (pathogenic-class 5 or likely pathogenic-class 4 variants, summarized in Table 3 and in Figure 4).…”
Section: Identification Of Two Novel Intronic Variants Affecting Fmr1mentioning
confidence: 99%